Programming Pearls - Jon Bentley (Pearson Education, 2007)
n this revision, the first in 14 years, Bentley has substantially updated his essay to reflect current programming methods and environments. In addition, there are three new essays on (1) testing, debugging, and timing; (2) set representations; and (3) string problems. All he original programs have been rewritten, and an equal amount of new code has been generated. Implementations of all the programs, in C or C++, are now available on the Web. What remains the same in this new edition is Bentleys focus on the hard core of programming and his delivery of workable solutions to those problems. Whether you are new to Bentleys classic or are revisiting his work for some fresh insight, the book is sure to make your own list of favorites.